KEBUTUHAN BELAJAR TENAGA PENGELOLA PERPUSTAKAAN DI UPT PERPUSTAKAAN UNIVERSITAS JEMBER - Khusnun Nadhifah (Jurnal Pustaka Ilmiah, 2019)
The learning needs of library management personnel at UPT Library of Jember University is a description of the level of concern and responsibility that become indicators of professionalism in work. Readers need a fast and accurate information service with respect to course materials, research, publications, journals, and more. Library as well as a container of various disciplines that also support science or as a means of educating the life of the nation especially in the field of education. It takes a study that can describe the level of learning needs of library managers. This study aims to identify the learning needs of library management personnel at UPT Library of Jember University.The research method uses descriptive design because it wants to describe the level of learning needs of the library management personnel. The population in this research is the entire library management staff at UPT Jember University Library obtained by total sampling or census technique. Using a closed questionnaire research instrument of 20 questions that describe the needs of the information of the reader.The result of the research has been done, it is known that the learning needs of library management staff in UPT Library of Jember University are in the category of Specialties, Very Good and Good as many as 30 personnels (69,76%). Learning Needs Good Enough, Enough, Less and Very Less as many as 13 personnels (30.24%). The maximal, minimum, median, mode, mean and standard deviation values are as follows: 95, 45, 50, 80, 74.77 and 13.68Motivation and guidance to improve the learning needs of library management personnel need to be done with various learning strategies, especially on the learning needs group Good Enough, Enough, Less and Very Less.